National Landscape of Hospitalizations in Patients with Left Ventricular Assist Device. Insights from the National Readmission Database 2010–2015. Issue 10 (November 2020) - Lemor, Alejandro; Michaels, Alexander; Al-Darzi, Waleed; Hernandez, Gabriel A.; Nasr, Youssef; Villablanca, Pedro; Blumer, Vanessa; Tita, Cristina; Williams, Celeste T.; Selektor, Yelena; Lanfear, David E.; Lindenfeld, JoAnn; et al.
Abstract : The number of patients with left ventricular assist devices (LVAD) has increased over the years and it is important to identify the etiologies for hospital admission, as well as the costs, length of stay and in-hospital complications in this patient group. Using the National Readmission Database from 2010 to 2015, we identified patients with a history of LVAD placement using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code V43.21. We aimed to identify the etiologies for hospital admission, patient characteristics, and in-hospital outcomes. We identified a total of 15, 996 patients with an LVAD, the mean age was 58 years and 76% were males. The most common cause of hospital readmission after LVAD was heart failure (HF, 13%), followed by gastrointestinal (GI) bleed (11.8%), device complication (11.5%), and ventricular tachycardia/fibrillation (4.2%). The median length of stay was 6 days (3–11 days) and the median hospital costs was $12, 723 USD. The in-hospital mortality was 3.9%, blood transfusion was required in 26.8% of patients, 20.5% had acute kidney injury, 2.8% required hemodialysis, and 6.2% of patients underwent heart transplantation. Interestingly, the most common cause of readmission was the same as the diagnosis for the preceding admission. One in every four LVAD patients experiences a readmission within 30 days of a prior admission, most commonly due to HF and GI bleeding. Interventions to reduce HF readmissions, such as speed optimization, may be one means of improving LVAD outcomes and resource utilization.